Dionysios I. von Syrakus. Modell einer Machtergreifung - von Ungern-Sternberg, Jürgen (Hyperboreus, 2020)
For the rise of the young Dionysius from a secretary of the generals (στρατηγοί) to the ruler of Syracuse, we have the detailed report of the historian Diodorus, which is important and rich in substance because it goes back to a man in the intimate circle of friends of the tyrant, Philistus. A close interpretation of the account shows in great completeness all the steps, which were necessary for coming to power. In the same time, it is demonstrated that Dionysius and his friends were able to draw various lessons from history. In their turn, they inﬂuenced decisively the later Greek theories about monarchy.